The problem of the inflation of rights and the incongruences of minimalist theories - Zezza, Michele (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2015)
The subject of this paper focuses on the changes in the “Fundamental Rights” system in today’s constitutional governments, namely those Liberal democracies that since WWII based their foundation on a written, rigid and extended constitution. Such constitution was intended to have a planning and directional function and was supervised by jurisdictional control provided by constitutional legitimacy. Also, such model has a wide and substantial ethical content: a set of values, principles, interests, assets and rights that implied relevant constraints to decisions lawfully taken by the legislative body the analysis concentrates on the issue of the anomic expansion (inflation, or proliferation) of rights and on the debate concerning the saturation of their juridical scope. The main goal of this article is to demonstrate how such frame fundamentally lacks a reconstructive-explanatory value: namely, this is an approach of moral and political philosophy unaware of any legal positive material; as such it can’t be accepted as a hypothesis of reconstruction of the structural features of the constitutional State of law. Considering this reformation of the Fundamental rights, it’s meant to argue the superiority of a pluralist and inclusive conception.